Pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), PertumbuhanDana Pihak Ketiga (DPK), Biaya Operasional terhadap Pendapatan Operasional (BOPO)Terhadap Likuiditas Yang Diukur Dengan Loan to Deposit Ratio Pada Perusahan Perbankan Yang Tercatat di Bursa Efek Indonesia - Kartini Kartini; Anis Nuranisa (Unisia, 2014)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), the growth of third party funds (DPK), Operating Expenses to Operating Income (BOPO) for liquidity as measured by the Loan to Deposit Ratio (LDR) on banking company listed on the Indonesia Stock Exchange (IDX). The population in this study is a banking company listed on the Stock Exchange in 2013 through 2014. This study used purposive sampling method, based on the research it is known there are 33 banks go public listed in Indonesia Stock Exchange (IDX) from 2013 through 2014 , of 33 Bank is only 10 banks that meet the criteria. Data used in this research is secondary data taken through The Corner of Indonesia Stock Exchange UII.The test results showed that the variable Capital Adequacy Ratio (CAR) and significant effect on the loan to deposit ratio (LDR), while non-performing loan (NPL), the growth of third party funds (DPK), and Operating Expenses to Operating Income (BOPO) does not affect the Loan to Deposit Raio (LDR).